The relationship between working condition and job satisfaction amongst technical employees at Sum Hing Engineering Works Sdn.Bhd. / Nurafiqah Rasul - Rasul, Nurafiqah (Faculty of Business and Management, 2018)
Working condition has recently become an important issue in organization. The objectives of this study were to examine the relationship between working condition and job satisfaction amongst technical workers at Sum Hing Engineering Works Sdn. Bhd. The researcher focusing on working condition which is job demand, job control and social support that influence job satisfaction. In this study, correlation study was used as a research design. About 118 technical employees at Sum Hing Engineering Works Sdn. Bhd. were selected. The data was collected through a set of questionnaires. The Statistical Package in the Social Science software (SPSS) version 20.0 was used in other to analyze the data. The result of the study showed that most of the respondents slightly agreed with the working condition in their workplace. In addition all factor of working condition have significant positive relationship with job satisfaction. The study also showed all hypotheses were accepted. Job demand showed has the most impact toward job satisfaction. Based on the result, the researcher recommend that the organization should focused more on job control and social support in order to increase employee’s job satisfaction. Future study should be made on wider and geographically diverse group of respondent because it would expand the research sample, reliability and validity of the population.